Peran Keujren Blang dalam Melestarikan Budaya Tron U Blang - Nasyua Paizah; Nabila Maulida Aprilia; Nisrina; M.Ardila Armanda; Sopar (Sci-tech Journal, 2025)
Keujren blang is an example of the natural wealth owned by the Aceh region. This area has a unique culture and biodiversity, with various types of plants and animals living in it. Keujren blang also has important ecological, economic, and social values for the local community. Gampong Ujong Drien is one of the areas in Aceh that has extensive and diverse keujren blang. However, keujren blang in this area faces various threats, such as environmental change, deforestation, and unsustainable human activities. Therefore, research on keujren blang in Gampong Ujong Drien is very important to be carried out in order to understand the uniqueness and biodiversity of keujren blang and identify the threats faced by this ecosystem.Keywords: keujruen blang, ujung drien